Examining food safety practices of food delivery riders using the KAP theory / Nurul Syazana Hishamuddin, Eshaby Mustafa and Mohamad Qamarul Sadiman - Hishamuddin, Nurul Syazana; Mustafa, Eshaby; Sadiman, Mohamad Qamarul (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
The COVID-19 pandemic has prompted consumers to consistently pay attention to the safety of their environment, including the source from which they obtain their food. Because of this, the volume of food orders has increased as people are reluctant to dine outside their homes. However, there is a lack of understanding of food safety practices developed by online takeaway food ordering suppliers (OTFOS). Although OTFOS are educated on food safety, it is not known whether they practice them in the work environment. Therefore, this conceptual paper aims to provide an insight into the importance of applying appropriate knowledge, attitudes, and practices (KAP), especially among food delivery riders who work for OTFOS. The study will focus on food safety issues, especially food safety procedures. In addition, this study is relevant to academics as it contributes to KAP theory, particularly food safety and hygiene in the online takeaway food ordering (OTFO) sector. The findings will help the government and suppliers to fully emphasise the need for comprehensive food safety knowledge and practices among OTFO stakeholders.